Morphologic and cytogenetic variables affect the flow cytometric recovery of plasma cell myeloma cells in bone marrow aspirates. (30th July 2015) - Cogbill, C. H.; Spears, M. D.; Vantuinen, P.; Harrington, A. M.; Olteanu, H.; Kroft, S. H.
Summary: Introduction: It is widely recognized that plasma cells (PCs) are under‐represented in flow cytometry (FC) studies, but the causes of this phenomenon are poorly understood. We sought to study potential variables that affect PC recovery by flow cytometry (FC) in the analysis of plasma cell myeloma (PCM). Methods: We retrospectively performed PC differential counts and morphologic assessment on PCM peripheral blood (PB) smears, bone marrow (BM) aspirate smears and posterythrocyte lysis cytospins. PCs were enumerated by FC, excluding erythroid events/debris, and were defined as CD38(bright+), CD45(dim to negative) events. PC recovery was calculated as follows: cytospin/aspirate, FC/aspirate, and FC/cytospin. Results: Sixty‐four BM analyses from 42 patients showed a mean aspirate PC% of 32.9 ± 23.2%. The mean PC% decreased in both the cytospin (10.9%) and by FC (8.2%). The difference between PC% in the cytospin and by FC was statistically significant ( P  < 0.03). Mature PC morphology and lower aspirate PC% had poorer recovery ( P  < 0.05) but higher‐risk cytogenetics (deletions of 13q and TP53 ) was associated with increased PC recovery. Immunophenotype, heavy chain type, and treatment did not affect PC recovery. PB specimens had superior recovery compared with BM samples. Conclusions: Similar to prior reports, the greatest loss of PC in BM evaluation occurs between the aspirate and postlysis specimens; however, a small amount occurs from further processing. Additional morphologic and cytogenetic factors also appear to influence recovery in addition to overall PC%.